Programa educativo sobre o desenvolvimento infantil para mães sociais. - Perez, Renata Reis Munhoz (2003)
This work had for objectives to develop, to apply and to evaluate an educational program on the infantile development, from 0 to 2 years, for social mothers of the nursery of the orphanage. They announced of this research three social mothers that work with children from 0 to 2 years. For the materialization of the proposed objective, the work was divided in nine stages. In the first stage, it was made an observation of the routine of the social mothers' performance in the bath activities and change of clothes, hour of feeding and activities of play, serving as base for the development of the program. In the second stage, the questionnaire 1 was applied (pré-test). In the third, a program was implemented with the elaboration and application of the first four classes, with the duration of one month. In the fourth stage, it was applied the questionnaire 1 again (powder-test). In the fifth stage, the questionnaire 2 was applied (pré-test). In the sixth stage, they were applied the last four classes of the program, with the duration of one month. In the seventh stage, it was accomplished the application of the questionnaire 2 again (powder-test). In the eighth stage the mothers' new filmings were accomplished with the children at the end of the course. Therefore after, the ninth stage was accomplished (Follow-up) that consisted in the evaluation of the program during the three months after the end of the interventions. The results showed that the social mothers don't obey her/it any acting pattern with relationship the children's observation. The one that the work showed was individual differences in the form of working with the children in the routine situations. Besides, they lack important information for the social mothers concerning the development in general of the children in that phase, and the importance of their proximity in the first years of the baby's life. Finally, the studiousness of the program showed to be necessary and important to minimize such problems. There was change in the degree of the mothers' knowledge on the infantile development and in the interactions with the children, and this can influence on a larger entail among mother-child.